The associations between BMI, body appreciation, body image flexibility, sleep duration and loneliness in workers in southern China - Juncheng Zhao; Chunmei Wu; Yanfang Gao; Ming Hao; Xiaokang Zhang (BMC Public Health)
Abstract Background Loneliness is a growing public health problem worldwide that can affect mental and emotional health and increase mortality. This study examined the relationship between body mass index (BMI), body image flexibility, body appreciation, and loneliness among Chinese workers, aiming to propose effective measures for reducing loneliness and promoting mental health. Methods A total of 464 workers were recruited for this study. Participants completed the Chinese version of the Body Image Acceptance and Action Questionnaire, the BMI measure, a Standard Chinese translation of the Body Appreciation Scale, and the Chinese version of the short-form UCLA Loneliness Scale (ULS-8). Statistical analyses were performed using SPSS. Results There were gender differences in body appreciation and body image flexibility scores were observed. Loneliness levels were higher among female workers than male workers. Male workers scored higher than female workers in body appreciation. Female workers scored significantly higher than male workers in body image flexibility and loneliness. Based on multiple regression analyses of the factors affecting loneliness scores, body image flexibility score (β = -0.19, p < 0.01) and body appreciation score (β = -0.25, p < 0.01) were significant predictors of loneliness. Conclusion As middle-aged individuals exhibit higher levels of loneliness. Policymakers should prioritize workplace mental health programs that combine body positivity workshops, sleep hygiene education, and peer support networks. For example, incorporating body image flexibility training into existing employee wellness programs to reduce isolation. In addition, public campaigns to combat weight stigma, such as media literacy programs, are urgently needed to address the social factors that contribute to loneliness.